Identification of Brachypodium distachyon B3 genes reveals that BdB3-54 regulates primary root growth - Jie Guo; Hanxiao Liu; Keli Dai; Xiangyang Yuan; Pingyi Guo; Weiping Shi; Meixue Zhou; Meixue Zhou (Frontiers in Plant Science, 2022)
B3 is a class of plant-specific transcription factors with important roles in plant development and growth. Here, we identified 69 B3 transcription factors in Brachypodium distachyon that were unevenly distributed across all five chromosomes. The ARF, REM, LAV, and RAV subfamilies were grouped based on sequence characteristics and phylogenetic relationships. The phylogenetically related members in the B3 family shared conserved domains and gene structures. Expression profiles showed that B3 genes were widely expressed in different tissues and varied in response to different abiotic stresses. BdB3-54 protein from the REM subfamily was located in the nucleus by subcellular localization and processed transcriptional activation activity. Overexpression of BdB3-54 in Arabidopsis increased primary root length. Our study provides a basis for further research on the functions of BdB3 genes.